Anisotropic factors affecting the ductile-brittle transition of rolled‑tungsten after different recrystallization treatments. (December 2022) - Geng, Xiang; Wang, Wan-Jing; Li, Qiang; Xie, Chun-Yi; Wang, Ji-Chao; Zhou, Hai-Shan; Luo, Guang-Nan
Abstract: Ductile-brittle transition temperature (DBTT) is a critical property of tungsten (W) materials for their application in a fusion reactor. The mechanism of ductile-brittle transition (DBT) has been the focus of debate in past decades. In this work, four-point bending test (4PBT) was performed to explore the controlling factors in different directions relative to the rolling direction. Opposite DBTT shifting trend in different directions after different recrystallization treatments indicated the diverse controlling factors of DBTT in rolled-W. Combined with microstructure analyses, the dislocation activity is considered the main controlling factor of DBTT in parallel to the rolling direction. For the samples perpendicular to the rolling direction, the change of DBTT is strongly correlated with the fracture mode. This study revealed the controlling factor of DBTT is anisotropic related to rolling direction after different recrystallization treatments. Highlights: Anisotropic controlling factors of DBT after different recrystallization treatments are related to the anisotropy of rolled-W. The texture produced by rolling is more conducive to dislocation slip in RD direction. The change of DBTT is strongly correlated with the fracture mode in TD direction.